2011
DOI: 10.1007/s10008-011-1501-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic oxidation of glucose on nanoporous gold membranes

Abstract: With characteristic of structural integrity and high surface area, nanoporous gold (NPG) prepared by dealloying method is proposed to be a highly sensitive catalyst for glucose electrooxidation. It can be found that a-NPG which obtained by electrochemical corrosion method has the highest sensitivity for glucose electrooxidation among the three studied samples. Under alkaline conditions, the catalytic current density of a-NPG is over 1.5 times and 17 times higher than that of f-NPG (prepared by free corrosion) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…In 0.1 M NaOH, planar gold displayed an onset potential of -0.6 V (vs. SCE) for glucose 5 oxidation, while -0.9 V (vs. SCE) for NPG with 12 nm pores [88]. …”
Section: Nonenzymatic Glucose Biosensors 30mentioning
confidence: 99%
“…In 0.1 M NaOH, planar gold displayed an onset potential of -0.6 V (vs. SCE) for glucose 5 oxidation, while -0.9 V (vs. SCE) for NPG with 12 nm pores [88]. …”
Section: Nonenzymatic Glucose Biosensors 30mentioning
confidence: 99%
“…The ability to use an electrode that has an electrochemically useful surface area that is 10-100 times larger than a traditional electrode thus offers much promise. Examples of small molecules that have been studied include dopamine [144], ascorbic acid [144], hydrogen peroxide [143,145], nitrite [146], cysteine [147], nitrophenol [148,149], hydrazine [150], and glucose [151].…”
Section: Small Molecule Sensingmentioning
confidence: 99%
“…At a traditional planar electrode, this analyte is difficult to be measured and thus, an enzyme (e.g., glucose oxidase) is often incorporated into the electrochemical sensor platform [152,153]. Recently, however, the nonenzymatic oxidation of glucose on nanoporous gold has been described in a number of reports [79,151,[154][155][156][157]. In 2008, Yin et al reported on the oxidation of glucose on nanoporous gold with different ligament sizes (6-250 nm) and also studied the effect of residual silver (6.8 to 37.9%) [154].…”
Section: Small Molecule Sensingmentioning
confidence: 99%
See 2 more Smart Citations